2013
DOI: 10.1111/ene.12280
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glucose level adversely affects infarct volume growth and neurological deterioration in non‐diabetic stroke patients, but not diabetic stroke patients

Abstract: Glucose level appears to influence infarct volume growth and neurological deterioration, particularly in non-diabetic patients with ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 23 publications
6
52
2
5
Order By: Relevance
“…13 But in the recent studies, it has been seen that increased mortality is seen in patients with stroke and stress hyperglycemia. [14][15][16] In our study, there was as slight preponderance of males over females, though this was not found to be significant. Among the stroke patients the age group where diabetes was more common was 51-60 years in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…13 But in the recent studies, it has been seen that increased mortality is seen in patients with stroke and stress hyperglycemia. [14][15][16] In our study, there was as slight preponderance of males over females, though this was not found to be significant. Among the stroke patients the age group where diabetes was more common was 51-60 years in our study.…”
Section: Discussioncontrasting
confidence: 81%
“…Glucose was significantly higher with IS-END [2, and ICH-END [37], which may have numerous explanations including poorer collateral flow, endothelial damage, increased oxidative stress and lactate, haemorrhagic transformation and dysregulation of glucose energy metabolism [38]. This was mirrored in glycosylated haemoglobin A1c, a marker of chronic raised glucose, also predicting END [9,23,25,26,29,30,35,39] [5K].…”
Section: Metabolic Biomarkersmentioning
confidence: 99%
“…3 Furthermore, an elevated glucose level is associated with increased infarct volume and neurological deterioration in patients without diabetes mellitus, but not in patients with diabetes mellitus. 4 These findings indicate that acute hyperglycemia may be more harmful in nondiabetic cases. In animal models of ischemic stroke, induction of hyperglycemia before stroke was significantly associated with increased infarct volume 5,6 and blood-brain barrier (BBB) permeability and hemorrhagic transformation with or without thrombolysis.…”
mentioning
confidence: 96%